Identification Customer Needs of Shuttle Travel by Using Servqual and Kano Methods - Syeren Anastasya; Sari Wulandari; Agus Achmad Suhendra (School of Industrial and System Engineering, Telkom University, 2023)
Bhinneka Shuttle is a companies which is engaged in customer delivery transportation services andwas founded in 1972. Throughout 2022, Bhinneka Shuttle experienced an unstable amount of revenueand did not achieve the target number of passengers. Based on the results of a comparison of the fourbranches of Bhinneka Shuttle outlets in Bandung City, it is known that Bhinneka Shuttle Mekar Wangineeds to get improvement priority. This is supported by the low Google review rating and manycomplaints about the performance of the services provided. Customer dissatisfaction and highcompetition in the transportation business require Bhinneka Shuttle Mekar Wangi to improve andincrease the quality of its services. This study aims to identify True Customer Needs by using theintegration of the Servqual method and the Kano Model so that priority attributes are obtained forimprovement and become basic recommendations for designing company service qualityimprovements. The attribute needs were obtained by conducting a study of the literature and Voice ofCustomer which were classified into five Servqual dimensions, that is Reliability, Comfort, Extent ofService, Safety, and Affordability (RESCA). According to research result, 11 attributes TrueCustomer Needs that needed to be improved which states that the services provided by BhinnekaShuttle still does not provide satisfaction to consumers. Bhinneka Shuttle are suggested to pay moreattention to weak attributes that are included in the must be category because they are basic need incompany’s services